Pemantauan Keragaman Hutan Menggunakan Landsat 8 OLI-TIRS di Provinsi Kalimantan Tengah - Raden Mas Sukarna; Antonius Triyadi; Hari Prakasa; Nisfiatul Hidayat; Alpian Alpian (HUTAN TROPIKA, 2023)
Land cover changes are difficult to review caused by large areas where the rate of its changes can not be controlled. Its changes need to be learned to obtain information of forest condition. The purpose of this study is to analyze land cover changes in 2015 to 2019 using Landsat 8 OLI-TIRS imagery including to know the vegetation diversity in Kapuas Tengah Sub District, Central Kalimantan Province. The results showed that during this time there are degradation of dense forest to shrubs approximately 7,857.061 ha and reforestation of medium forest to dense forest was 7,220.401 ha. The increasing of land cover is also occurred from open area to forest approximately 277.248 ha through palm oil plantations. The accuracy level of land cover classification is still not maximum. The results of the vegetation analysis also show that at each level of forest growth there are variations in species, which are dominated by red meranti (Shorea johorensis Foxw), white ketumbu, kalapapa and sampahiring (Cyperus Sp.). Diversity index and species richness index are categorized as low to moderate. Whereas the species evenness index is high category with index value of 1.